Numerical Simulations of Seasonally Oscillated Groundwater Dynamics in Coastal Confined Aquifers. Issue 4 (7th August 2019) - Qu, Wenjing; Li, Hailong; Wang, Chaoyue; Zheng, Chunmiao; Wang, Xuejing; Zhang, Yan
Abstract: Studies investigating the effects of inland recharge on coastal groundwater dynamics were carried out typically in unconfined aquifers, with few in confined aquifers. This study focused on the groundwater dynamics in confined aquifers with seasonally sinusoidally fluctuated inland groundwater head and constant sea level by numerical simulations. It is known that the mixing zone (MZ) of saltwater wedge in response to the seasonal oscillations of inland groundwater head swings around the steady‐state MZ. However, our simulation results indicate that even the most landward freshwater‐saltwater interface over a year is seaward from the steady‐state location when the hydraulic conductivity K is ≤10 −4  m/s under certain boundary conditions with given parameter values. That is, seasonal oscillations of inland groundwater head may reduce seawater intrusion in confined coastal aquifers when K  ≤ 10 −4  m/s. Sensitivity analysis indicates that for aquifers of K  ≤ 10 −4  m/s, the larger the inland head fluctuation amplitude is, the less the seawater intrudes. This is probably due to the reason that the seawater intrusion time decreases with the increase of fluctuation amplitude when K  ≤ 10 −4  m/s. Numerical simulations demonstrate that seasonal inland groundwater head oscillations promote the annual averaged recirculated seawater discharge across the seaward boundary. Abstract : Article impact statement : Seasonally oscillated inland water level may prevent seawater intrusion in confined aquifers when K  ≤ 10 −4  m/s under certain conditions.